(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Jhumpa Lahiri is known for her ability to intricately weave together themes of identity, family, culture, and belonging in her writing. In her novel The Lowland, Lahiri further explores these themes through the lens of the immigrant experience and the impact of historical events on individuals and families. This research paper examines Lahiri’s use of language and the portrayal of cross-cultural themes in The Lowland, highlighting the ways in which she captures the complexity and nuance of characters navigating different worlds. In The Lowland, Jhumpa Lahiri masterfully employs language and cross-cultural themes to explore the intricate interplay between personal and political histories. This research paper delves into Lahiri's narrative techniques, symbolic imagery, and the expression of cultural identity, highlighting how these elements contribute to the novel's depth and resonance. By utilizing dual narrative perspectives and a non-linear timeline, Lahiri presents a multifaceted view of the characters' lives, emphasizing the enduring impact of past events on their present. The novel's vivid symbolism, particularly through the contrasting landscapes of Calcutta and Rhode Island, underscores the characters' internal and external conflicts.